2008
DOI: 10.1002/er.1459
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of steam reforming of ethanol for hydrogen generation

Abstract: SUMMARYThermodynamic equilibrium of ethanol steam reforming has been studied by Gibbs free energy minimization method for hydrogen production in the ranges of water-to-ethanol ratio from 0 to 20, reaction temperature from 400 to 2000 K, pressure from 1 to 60 atm, argon-to-ethanol ratio from 0 to 100. The optimal conditions suitable for the use in molten carbonate fuel cell and solid oxide fuel cell were obtained as follows: 900-1200 K, water-to-ethanol ratio of 3:6, and 1 atm. Under the optimal conditions, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 30 publications
5
45
1
1
Order By: Relevance
“…In contrast to Vagia and Lemonidou, Aktaş et al [85] reported a higher hydrogen mole fraction even at pressure as high as 30 atm in SR of model bio-oil components like isopropyl alcohol, lactic acid and phenols. These results are in contradiction to most of the authors in SR of various liquid fuels like ethanol, glycerol and butanol [16,43,63]. The authors reported the best operating conditions a steam-to-fuel ratio of 4, 5 and 9 at 15 1200 K for isopropyl alcohol, lactic acid and phenols respectively.…”
Section: Thermodynamic Investigationscontrasting
confidence: 58%
See 1 more Smart Citation
“…In contrast to Vagia and Lemonidou, Aktaş et al [85] reported a higher hydrogen mole fraction even at pressure as high as 30 atm in SR of model bio-oil components like isopropyl alcohol, lactic acid and phenols. These results are in contradiction to most of the authors in SR of various liquid fuels like ethanol, glycerol and butanol [16,43,63]. The authors reported the best operating conditions a steam-to-fuel ratio of 4, 5 and 9 at 15 1200 K for isopropyl alcohol, lactic acid and phenols respectively.…”
Section: Thermodynamic Investigationscontrasting
confidence: 58%
“…Wang and Wang [16] calculated a 60.52-83.58% hydrogen yield (EQ-5) with 32.82-79.60% carbon monoxide yield at steam to S/EtOH between 3-6 at 900-1200 K in thermodynamic analysis of SRE. The authors reported that, as expected from Le Chatelier's principle, increase in pressure restrained hydrogen formation as a result of shift in the equilibrium to reactants in the SR reactions.…”
Section: Thermodynamic Investigationsmentioning
confidence: 99%
“…Equilibrium compositions were calculated by minimizing the Gibbs free energy with software CHEMCAD (Wang and Wang 2008). The errors of the calculated results were lower than 0.5 · 10 -8 .…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
“…Thermodynamic analysis for ethanol reforming has been carried out to understand the effect of operating conditions on product selectivities and yields [41][42][43]. A number of studies have focused on developing Langmuir-Hinshelwood-Hougen-Watson (LHHW) or Eley-Rideal rate expressions followed by data fitting of the kinetic parameters [44][45][46][47].…”
Section: Computational Studiesmentioning
confidence: 99%